Involvement of HbMC1-mediated cell death in tapping panel dryness of rubber tree (Hevea brasiliensis). (29th November 2018) - Liu, Hui; Wei, Yongxuan; Deng, Zhi; Yang, Hong; Dai, Longjun; Li, Dejun
Abstract: Tapping panel dryness (TPD) causes a significant reduction in the latex yield of rubber tree ( Hevea brasiliensis Muell. Arg.). It is reported that TPD is a typical programmed cell death (PCD) process. Although PCD plays a vital role in TPD occurrence, there is a lack of detailed and systematic study. Metacaspases are key regulators of diverse PCD in plants. Based on our previous result that HbMC1 was associated with TPD, we further elucidate the roles of HbMC1 on rubber tree TPD in this study. HbMC1 was up-regulated by TPD-inducing factors including wounding, ethephon and H2 O2 . Moreover, the expression level of HbMC1 was increased along with TPD severity in rubber tree, suggesting a positive correlation between HbMC1 expression and TPD severity. To investigate its biological function, HbMC1 was overexpressed in yeast ( Saccharomyces cerevisiae ) and tobacco ( Nicotiana benthamiana ). Transgenic yeast and tobacco overexpressing HbMC1 showed growth retardation compared with controls under H2 O2 -induced oxidative stress. In addition, overexpression of HbMC1 in yeast and tobacco reduced cell survival after high-concentration H2 O2 treatment and resulted in enhanced H2 O2 -induced leaf cell death, respectively. A total of 11 proteins, rbcL, TM9SF2-like, COX3, ATP9, DRP, HbREF/Hevb1, MSSP2-like, SRC2, GATL8, CIPK14-like and STK, were identified and confirmed to interact with HbMC1 by yeast two-hybrid screening and co-transformation in yeast. The 11 proteins mentioned above are associated with many biological processes, including rubber biosynthesis, stress response, autophagy, carbohydrate metabolism, signal transduction, etc. Taken together, our results suggest that HbMC1-mediated PCD plays an important role in rubber tree TPD, and the identified HbMC1-interacting proteins provide valuable information for further understanding the molecular mechanism of HbMC1-mediated TPD in rubber tree.